VELOCITY PROFILE VISUALIZATION OF WATER NATURAL PERCOLATION IN A POROUS MEDIUM - França, A. C.; Carrocci, L. R.; Siqueira, A. F. (Revista de Engenharia Térmica, 2009)
This paper aims to show the profile and the behavior of the velocity of the water flow through a porous medium composed of clay and sand aggregated by burning in an oil furnace. The work models mathematics based on the Navier-Stokes differential equation, which represents the behavior of the water velocity flow in porous medium taking into account parameters of a low velocity laminar flow, increased load loss value and Number of Reynolds > 1. Physical phenomena such as porosity, permeability, particles arrangement, radius and wet perimeter are considered in the equation. The study shows the three-dimensional profile of the water percolation velocity which, originated from the capillary phenomenon, causes a sum of the tensions of increased values able to produce cracks in the medium structure. And, differently from filtration phenomenon, which overcomes the capillarity of the medium by the gravitational force or by efforts applied aiming to increase the flow velocity, the natural percolation opposes to the gravity and to the surrounding pressure moving slowly, reaching the flow at 30 and 40 centimeters depending on the permeability of the porous medium.